PROMOSI JABATAN DAN ROLLING JABATAN/MUTASI DALAM PEMBERDAYAAN SDM DI MA AL AMIRIYYAH BLOKAGUNG BANYUWANGI - Amirotun Nahdliyah; Lailatul Izzah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2022)
High work performance will have an impact on high work results. Advanced educational institutions will be meaningless without the welfare of their employees. If employees feel more and more welfare from the results of their hard work, then employees do not hesitate to continually increase their sense of ownership and high responsibility for the sake of educational institutions and for their welfare. Therefore promotion and rolling positions/mutations in empowering human resources in educational institutions are significant to support one of the roles in the success of an organization/educational institution. This study uses a descriptive qualitative research method using observation, interviews/interviews, and documentation as data collection techniques. The data sources of this research inc 1) person, namely, (a) the head of the madrasa, (b) waka of the curriculum, and (b) supervisor. 2) place, namely, at MA Al-Amiriyyah Blokagung Banyuwangi. Data analysis techniques, drawing conclusions or verification. This study also checked the validity of the data by triangulation of sources, methods, and investigations. The results of his research: (1) the implementation of promotions and rolling positions at MA AL Amiriyyah includes several basic foundations based on experience, skills, and a combination of experience and skills, as well as using a merit system for the implementation of rolling positions, (2) the contribution of promotions and position rolling includes developing the vision and mission of the madrasa itself as well as producing certain jobs/angels so that the institution can provide recognition of positions and greater service rewards to employees whose performance is increasingly high. (3) evaluation of job promotions and rolling positions, namely with supervision from the institution as well as holding trainings and workshops for teachers and employees as well as seeing RKM for one year.